Antinociceptive Effect of Nyctanthes arbor-tristis Linn. Leaves on Sciatica Pain Induced by Chronic Constriction Injury - Nishtha Sahu; M D Kharya (Current Research in Pharmaceutical Sciences, 2015)
Nyctanthes arbor-tristis Linn. Commonly known as Harsingar(English:Night Jasmine), is a well documented plant. The decoction of the leaves of Nyctanthes arbor-tristis Linn. is widely used in Ayurvedic System of medicine for treatment of arthritis, fevers, various painful conditions and as a laxative. In present study was designed to evaluate the use of Nyctanthes arbor-tristis in sciatica pain. Swaras from the leaves of Nyctanthes arbortristis at the dose (10ml/kg, orally) significantly attenuated hyperalgesia (Hot-plate test) when compared with sham control measured on day 7,9,11,13,15,17 after chronic constriction injury.